Understanding jumping to conclusions in patients with persecutory delusions: working memory and intolerance of uncertainty. - Freeman, D; Startup, H; Dunn, G; Černis, E; Wingham, G; Pugh, K; Cordwell, J; Mander, H; Kingdon, D (2014)
BACKGROUND: Persecutory delusions are a key psychotic experience. A reasoning style known as 'jumping to conclusions' (JTC) - limited information gathering before reaching certainty in decision making - has been identified as a contributory factor in the occurrence of delusions. The cognitive processes that underpin JTC need to be determined in order to develop effective interventions for delusions. In the current study two alternative perspectives were tested: that JTC partially results from impairment in information-processing capabilities and that JTC is a motivated strategy to avoid uncertainty. METHOD: A group of 123 patients with persistent persecutory delusions completed assessments of JTC (the 60:40 beads task), IQ, working memory, intolerance of uncertainty, and psychiatric symptoms. Patients showing JTC were compared with patients not showing JTC. RESULTS: A total of 30 (24%) patients with delusions showed JTC. There were no differences between patients who did and did not jump to conclusions in overall psychopathology. Patients who jumped to conclusions had poorer working memory performance, lower IQ, lower intolerance of uncertainty and lower levels of worry. Working memory and worry independently predicted the presence of JTC. CONCLUSIONS: Hasty decision making in patients with delusions may partly arise from difficulties in keeping information in mind. Interventions for JTC are likely to benefit from addressing working memory performance, while in vivo techniques for patients with delusions will benefit from limiting the demands on working memory. The study provides little evidence for a contribution to JTC from top-down motivational beliefs about uncertainty.